Evaluasi Kesesuaian Penyimpanan Obat di Salah Satu Apotek Kota Cimahi - Elis Susilawati Elis Susilawati; ED. Yunisa Mega Pasha; Deti Siti Fatimah (Universitas Borneo Lestari, 2022)
Storage is one of the main factors in maintaining the quality of drugs by storing them appropriately and in accordance with established standards, if this is not done it will cause the quality of drugs to be not guaranteed during storage in pharmacies. The purpose of this study was to find out how to store drugs and how much is the percentage of suitability of the drug storage system in one of the pharmacies in Cimahi City. Drug storage in one of the pharmacies in Cimahi City is stored based on dosage form, therapeutic class, stability and arranged alphabetically with a dispensing system using the FEFO system. Drug storage systems in pharmacies that are in accordance with the Technical Guidelines for Pharmaceutical Service Standards are 86.36% while those that are not in accordance with the Pharmaceutical Service Standards Technical Instructions are 13.64% including adjacent LASA or NORUM storage, recording on stock cards that are less than optimal and no backup power. The storage system in one of the cimahi city pharmacies is not fully in accordance with the Technical Guidelines for Pharmaceutical Service Standards